Is the Association between Vitamin D and Cardiovascular Disease Risk Confounded by Obesity? Evidence from the Andhra Pradesh Children and Parents Study (APCAPS). - Christopher Paul Baker; Bharati Kulkarni; K V Radhakrishna; M S Charyulu; John Gregson; Mika Matsuzaki; Amy E Taylor; Dorairaj Prabhakaran; Raja Sriswan Mamidi; Jonathan Wells; Ian Wilkinson; Carmel McEniery; et al. (PLoS ONE)
Background Evidence of an association between serum vitamin D and cardiovascular disease risk is inconsistent and comes predominantly from studies in high-income settings. We assessed the association between serum levels of 25-hydroxyvitamin D3 (25(OH)D) and cardiovascular disease risk factors in a population of young Indian adults. Methods Cross-sectional analyses of data from APCAPS (Andhra Pradesh Children and Parents Study); a prospective birth cohort study in rural south India. Participants were 1038 (40.3% females) adults aged 18-24 years. Main outcome measures were blood pressures, fasting serum lipids (cholesterols and triglycerides), fasting glucose, insulin, measures of arterial stiffness (aortic augmentation index and aortic pulse wave velocity (aPWV)), carotid intima-media thickness, body mass index (BMI) and body fat (dual X-ray absorptiometry). Results Vitamin D deficiency (≤20ng/ml) was observed in 41.1% of this lean (mean BMI: 19.5) and active (mean minutes of moderate or vigorous physical activity per day: 186) population. Vitamin D deficiency was associated with higher median body fat in both males (15.9% body fat in vitamin D deficient males vs. 14.6% in non-deficient males, p<0.05) and females (29.1% body fat in vitamin D deficient females vs. 27.8% in non-deficient females, p<0.05) but no associations were observed between vitamin D deficiency and mean BMI or median fat mass index (FMI). Except a weak inverse association with fasting insulin in males, there was no clear association between serum vitamin D levels and cardiovascular disease risk factors in fully adjusted models. Conclusions We did not find clear evidence for an association between serum vitamin D levels and cardiovascular disease risk factors. Our results, consistent with the limited evidence from randomised trials of vitamin D supplementation and Mendelian randomisation experiments, suggest that the postulated link between serum vitamin D and cardiovascular disease may be non-causal. Instead, it may be attributable to confounding by lifestyle factors such as obesity and physical inactivity which may provide more fruitful targets for cardiovascular disease prevention.